2017
DOI: 10.3144/expresspolymlett.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

PE-HD fatigue damage accumulation under variable loading based on various damage models

Abstract: Abstract. Despite numerous studies on fatigue of polymer materials under variable loading, there is little work on highdensity polyethylene (PE-HD). In this context, an experimental analysis for determining the fatigue strength of PE-100, under constant and variable amplitude loading is presented. Further, the cumulative fatigue damage behavior of PE-100 was experimentally investigated. First, the fatigue curve (S-N: stress vs. number of cycles) was obtained in order to establish the fatigue life of PE-100 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…For instance, in Bourchak and Aid, 44 the values for high density polyethylene were determined as follows: σ = AN b , A = 33.5, b = −0.0728. It gives m = 1/ b = 13.7.…”
Section: Quality Of Repair and Role Of Defectsmentioning
confidence: 99%
“…For instance, in Bourchak and Aid, 44 the values for high density polyethylene were determined as follows: σ = AN b , A = 33.5, b = −0.0728. It gives m = 1/ b = 13.7.…”
Section: Quality Of Repair and Role Of Defectsmentioning
confidence: 99%
“…Many researchers have developed different fatigue damage criteria with certain levels of success. Bourchak and Aid [1] employed both the maximum stress criterion and the strain energy density criterion to estimate the fatigue damage of the polymer pipes. Their comparison showed different results between the two criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations indicated that the criteria were restricted to certain conditions. Bourchak and Aid, 20 for example, obtained different results for pipe fatigue using a strain energy density criterion and a maximum stress criterion. Artificial intelligence was also introduced to predict rubber fatigue damage and showed an excellent result 21 .…”
Section: Introductionmentioning
confidence: 99%